Сравнительный анализ магнитных систем электродвигателей с постоянными магнитами для электробуса - Гребеников, Виктор Владимирович; Прыймак, Максим Васильевич (НТУ "ХПИ", 2016)
Приведены результаты численного исследования влияния количества и высоты пазов статора, а также конфигурации постоянных магнитов в роторе на характеристики электродвигателей для городского электробуса. Показано, что при неизменных габаритных размерах электродвигателя путем увеличения высоты пазов статора и жидкостного охлаждения можно повысить электромагнитный момент и мощность электродвигателя. Выполнен расчет рабочих характеристик в программном пакете Infolytica MotorSolve, тепловой расчет выполнен в пакете Comsol.

The numerical investigation results of the influence of the number and the height of stator slots, as well as the configuration of the permanent magnets in the rotor on the characteristics of electric motors for urban electric bus are presented. It is shown, that at constant overall dimensions of the motor, the electromagnetic torque and motor power can be significantly improved by increasing of the stator slots height and liquid cooling. The optimum height of stator slots is found, at which the maximum electromagnetic torque and motor power at the set restrictions: induction in the magnetic circuit elements, the minimum diameter of the rotor provided its mechanical strength. To analyze the thermal state of electric motor models for operating with overload (at a current density of more than J = 5 A/mm2) a three-dimensional model of the electric motor sector is created. It is equal to one pole pitch, which takes into account the heat exchange processes not only in the volume of the electric motor, but in the system of liquid cooling. The simulation of electric motors with a different configuration of the magnetic system determined that the configuration with increased height of the groove and tangential magnetization of the magnets has the highest electromagnetic torque. This motor may be used instead of diesel engine for the average capacity bus. The operating characteristics have been calculated by Infolytica MotorSolve software package. Thermal calculation of electric motors with liquid cooling is made by Comsol software package.
Comparative analysis of magnetic electric motors with permanent magnets for electric buses
Keywords: постоянные магниты; высота паза статора; электромагнитный момент; рабочие характеристики; температура обмоток